2014
DOI: 10.1096/fj.14-250282
|View full text |Cite
|
Sign up to set email alerts
|

Feedforward activation of endothelial ENaC by high sodium

Abstract: Kidney epithelial sodium channels (ENaCs) are known to be inactivated by high sodium concentrations (feedback inhibition). Recently, the endothelial sodium channel (EnNaC) was identified to control the nanomechanical properties of the endothelium. EnNaC-dependent endothelial stiffening reduces the release of nitric oxide, the hallmark of endothelial dysfunction. To study the regulatory impact of sodium on EnNaC, endothelial cells (EA.hy926 and ex vivo mouse endothelium) were incubated in aldosterone-free solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 67 publications
3
36
0
Order By: Relevance
“…Interestingly, in the absence of aldosterone, high salt significantly increases the transcription of the MR [56] which is in agreement with the observation that salt loading decreases serum aldosterone, whereas MR activation in the target tissue is augmented [78]. In addition, the importance of the MR was demonstrated by the fact that aldosterone antagonism can prevent the effects of high Na + [56,87].…”
supporting
confidence: 86%
See 2 more Smart Citations
“…Interestingly, in the absence of aldosterone, high salt significantly increases the transcription of the MR [56] which is in agreement with the observation that salt loading decreases serum aldosterone, whereas MR activation in the target tissue is augmented [78]. In addition, the importance of the MR was demonstrated by the fact that aldosterone antagonism can prevent the effects of high Na + [56,87].…”
supporting
confidence: 86%
“…The MR as well as NEDD4-2 could also be detected in non-epithelial cells indicating that major prerequisites for the regulation of EnNaC along this pathway are given in endothelial cells [16,79,139]. Interestingly, in the absence of aldosterone, high salt significantly increases the transcription of the MR [56] which is in agreement with the observation that salt loading decreases serum aldosterone, whereas MR activation in the target tissue is augmented [78]. In addition, the importance of the MR was demonstrated by the fact that aldosterone antagonism can prevent the effects of high Na + [56,87].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In recent years, several studies have shown that comorbidities and mortalities are increased in PA patients compared to primary hypertensive patients (2,3). This was related to the detrimental effect of aldosterone itself in combination with the high-salt content of the current Western diet (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…As the handing of sodium is one of the main pathophysiological mechanisms regulating BP, a gene-dependent up-regulation of the ENaC activity may lead to sodium retention and consequently volume expansion ultimately affecting BP. Recently, a novel feed-forward activation of endothelial sodium channel (EnNaC) by sodium that contrasts ENaC feedback inhibition in the kidney has been proposed [30]. There is evidence that aldosterone increases EnNaC synthesis and membrane abundance as in the kidney.…”
Section: Discussionmentioning
confidence: 99%